2018
DOI: 10.1371/journal.pone.0208111
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of phthalate esters to lettuce (Lactuca sativa) and the soil microbial community under different soil conditions

Abstract: Phthalate esters (PAEs) are globally used plasticizers and typical endocrine disruptors that can readily accumulate in agricultural products and represent a substantial risk to human health via the food chain. The range of soil properties has an important influence on the expression of PAE toxicity, and the mechanisms by which soil physical and chemical properties affect the expression of toxicity of target PAEs to plants and microorganisms requires further investigation. Important soil factors affecting the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
(44 reference statements)
0
23
1
Order By: Relevance
“…DBP (99.1%) and DEHP (99.6%) certified reference materials (CRMs), assay kits (catalog number A052, inhibition and production of superoxide radical; A018, hydroxyl radical) and other analytical-grade reagents were purchased, and details of their use are as described in Ma et al [29].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DBP (99.1%) and DEHP (99.6%) certified reference materials (CRMs), assay kits (catalog number A052, inhibition and production of superoxide radical; A018, hydroxyl radical) and other analytical-grade reagents were purchased, and details of their use are as described in Ma et al [29].…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information about the selected soil can be found in Ma et al [29]. The soil background concentration levels of DBP and DEHP were 0.037 ± 0.002 and 0.087 ± 0.004 mg kg −1 (dry weight (DW), freeze dry basis), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total PAE concentrations ranged from 0.14 to 2.13 mg kg −1 (mean 0.99 mg kg −1 ) in soils and from 0.15 to 6.94 mg kg −1 (mean 1.49 mg kg −1 ) in vegetables [38]. The latest study, carried out in 2018, indicated that the toxicity to lettuce of DBP was higher than that of di-(2-ethylhexyl) phthalate (DEHP) in soil, and DBP treatment is associated with a decline in lettuce leaf size, as well as chlorophyll a and carotenoid content when compared to the control lettuce plants [39].…”
Section: Introductionmentioning
confidence: 99%